Accountability of village fund management in north malinau sub-district malinau district north Kalimantan province - Ridwan, Ridwan; Rulinawaty, Rulinawaty; Wijaya, Andi (Institute of Computer Science (IOCS), 2024)
To create accountability to the public, the role or participation of the community is needed to express their aspirations and contributions in the preparation of APBDes planning. The objectives of this research are 1). To analyze the implementation of accountability in village fund management in North Malinau District, Malinau Regency, North Kalimantan Province, 2). To analyze the obstacles in implementing accountability in managing village funds in North Malinau District, Malinau Regency, North Kalimantan Province. This research uses qualitative methods with data collection techniques using observation, interviews and documentation. The results in this study show that 1). Implementation of Village Fund Management Accountability in North Malinau District, Malinau Regency, North Kalimantan Province based on Accountability for Probity and Legality, Process Accountability, Program Accountability, and Policy Accountability is appropriate, 2). Obstacles to the Implementation of Accountability for Village Fund Management in North Malinau District, Malinau Regency, North Kalimantan Province, namely: Insufficient Human Resources and communication between the Village Government and the Community of Malinau Seberang Village and Kelayang Village is still one way.